Prevalence of otosclerosis among patients having deafness with intact tympanic membrane: a hospital based cross-sectional study - Gangyada, Pavan Kalyan Reddy; Kishve, Sanjay (International Journal of Research in Medical Sciences, 2023)
Background: Otosclerosis is a progressive and primary metabolic bone disease that results from abnormal bone remodeling of the otic capsule. Present study was undertaken to find out the prevalence of otosclerosis among patients having deafness with intact tympanic membrane. Aim was to find out association of otosclerosis with gender, correlation with age. To find out the type and degree of hearing loss. Methods: A total of 206 patients belonging to age group of 10-60 years fitting in the inclusion criteria were investigated for the presence of otosclerosis using Otoscopy, Pure Tone Audiometry, Tympanometry, HRCT temporal bone. Results: The prevalence of otosclerosis among our study population was 9.2% (3.9% were males and 5.3% were females). Association of otosclerosis with gender and correlation of otosclerosis with age was not significant. Conclusions: Our study showed presence of otosclerosis in 9.2%. Otosclerosis is not associated with age. Degree of hearing loss in patients diagnosed with otosclerosis was in between 30 to 50 dB and 89.4% of them had conductive deafness, 10.6% had mixed deafness.